COMPARATIVE STUDY: MISCONCEPTIONS ON PHOTOSYNTHESIS AND RESPIRATION CONCEPTS FROM PAST TO THE PRESENT - Jayanti, Puji (JPPS (Jurnal Penelitian Pendidikan Sains), 2019)
This study aimed to compare the past misconception problems in photosynthesis and respiration topics with the present cases in Indonesia. This descriptive study was undertaken to mainly describe the misconception on science learning from the past to the present times. Misconception test was used as the research instrument that was given to Indonesian students from four provinces namely East Java, South Sulawesi, South Sumatra, and Middle Kalimantan. This study used an experiment conducted in 1996, of which they were further compared with the present literatures about misconception in photosynthesis and respiration, including the data of pre-service teacher class obtained from 2010 to 2017. Results found that there was a similar misconception from 1996 to 2017 about photosynthesis and respiration. There was an indication that misconception in photosynthesis and respiration was not solved properly. This study suggested that the results could be used as an awareness for teachers in accordance with numbers of misconceptions in photosynthesis and respiration that have existed since long ago. Some actions were needed to overcome the misconceptions. One of the effort is by increasing students scientific reasoning skills. By increasing of students’ scientific reasoning skills, students will be able to interpret the information they got and using some evidence that related to evaluated the information truth. But the further research is needed to develop learning devices to train students’ scientific reasoning skills.